Advisory Aided System To Institute Of Higher Learning Based On Rules Based And Personality Assessment. - Osman, Mohd Azam; Sabudin, Maziani; Sharuddin, Shaiful Hisham (2007)
This paper discuss about the implementation and method used in AAISTIH. AISTIH is a web-based database system that uses rule-based and personality assessment in assisting student to apply the suitable course in institute of higher learning in Malaysia. It is a system designed with one thing in mind: to guide and advice students in selecting the courses tailored to their interests and qualifications based on students' academic qualifications and interests, using the rule-based approach in Artificial Intelligence